Mediation Model of Logistics Service Supply Chain (LSSC) Factors Affecting Organisational Performance - Abdulla, Mohamed Fuad Mohamed Hassan; Musa, Haslinda (International Journal of Sustainable Construction Engineering and Technology, 2022)
This paper presents the modelling of significant Logistics Service Supply Chain (LSSC) factors affecting Oil and Gas Industry performance in the UAE. Data collection involved the projects of Abu Dhabi National Oil Company (ADNOC). The model consisted of six independent constructs, one mediatorâ€™s construct and one dependent construct. The six independent constructs are Transport Management; Inventory Management; Order Process Management; Information Flow Management; Agility of logistics service and Integration capabilities of logistics. The mediator construct is logistic information, and the dependent construct is organization performance. The modelling used the AMOS-SEM approach, which indicates the graphical interaction of the factors toward the company performance. The data used to develop the model was gathered through the structured questionnaire survey amongst the selected respondents from the ADNOC oil and gas company in UAE, with a response rate of 90%, indicating strong participation from the population. Total 379 questionnaire forms were collected and used for analysis. The model was constructed according to the conceptual model and assessed at the measurement and structural level of the model. All the individual measurement models achieved the threshold criteria while the structural model reached the required fitness index. Then the model was run for hypothesis testing and found that four of the paths which are Transport Management; Inventory Management; Order Process Management; Information Flow Management have achieved a significant level. Also, Logistics Information Systems has not mediating effect to the relationship of Logistics Service Supply Chain (LSSC) factors affecting Oil and Gas Industry performance in the UAE.  This model contributed to the body of knowledge in presenting the relationship of factors affecting the performance of logistics in the Oil and Gas Industry. It is hoped that the oil and gas practitioners can gain from this model to be applied in their profession.